Urinary and fecal incontinence during sexual activity is common and bothersome among adults with spina bifida - Rothman, Joshua D.; Hensel, Devon J.; Wiener, John S.; Younsi, Nina; Stein, Raimund; Misseri, Rosalia; Szymanski, Konrad M. (Urology, 2024)
Objective - To evaluate the prevalence of and risk factors for urinary fecal incontinence (UI, FI) during sexual activity (UIS, FIS) among adults with spina bifida (SB). - Methods - An international online survey of adults with SB was administered through SB clinics and SB organizations via social media. Adults with a history of masturbation or partnered sexual activity were included. The primary outcome was ever experiencing UIS/FIS. Nonparametric tests and logistic regression were used for analysis. - Results - A total of 341 adults met inclusion criteria (median age: 36years, 59% female, 52% shunted, 48% community ambulators). Baseline UI in the last 4weeks was reported by 50% and FI by 41%. Nineteen (5%) had a urostomy. Eight (2%) had a colostomy. Overall, 93% had a history of partnered genital contact. Among adults without a diversion, UIS was more common than FIS (70% vs 45%, P < .001). Among adults without a urostomy, UIS was more common among women (76% vs 62%, P = .01) and those with baseline UI (84% vs 50%, P < .001). UIS was not associated with age, shunt, ambulatory, or catheterization status (P >=.32). On bivariate analysis, female sex and baseline UI were independent predictors of UIS (P <=.001). Among adults without a colostomy, FIS was associated with female sex (50% vs 39%, P = .046), baseline FI (59% vs 32%, P < .001), community ambulation (52% vs 40%, P = .04), but not age, shunt, or MACE status (P >=.27). On multivariate analysis, baseline FI was independently associated with FIS (P < .001). Among adults with UIS/FIS, 29% experienced UIS “almost always” to “always,” compared to 5% for FIS (P < .001). Virtually all adults found UIS/FIS bothersome (>=96% for each), even when incontinence occurred “almost never.” UIS/FIS mostly occurred before and/or during orgasm than afterward (P < .001). UIS was reported by 53% of adults with a urostomy (100% bothersome). FIS was reported by 38% of adults with a colostomy (100% bothersome). - Conclusion - Incontinence during sexual activity is a common problem for men and women with SB. Baseline incontinence is an independent, but not absolute, predictor of both. While FIS is less frequent than UIS, both are virtually always bothersome.
Gesehen am 22.01.2025